A mussel glue-inspired monomer-etchant cocktail for improving dentine bonding. (January 2022) - Xu, Rong-chen; Yu, Fan; Xiang, Guo-lei; Wang, Xiao-yu; Hu, Zun-han; Huang, Li; Liu, Lin; Duan, Long-yan; Liu, Qian; Niu, Li-na; Tay, Franklin R.; Chen, Ji-hua; et al.
Highlights: Dopamine methacrylamide (DMA) creates stable bonds with demineralised dentine collagen via covalent bonds, hydrogen bonds and van der WAALS forces in a wet environment. Incorporation of 5 mM DMA into phosphoric acid etchant improves the stability of the dentine collagen matrix. Incorporation of 5 mM DMA into phosphoric acid etchant inactivates collagenase activity. Etching dentin with 5 mM DMA-containing phosphoric acid prolongs the longevity of bonded dental restorations within a clinically-feasible time frame. Abstract: Objectives: The humid oral environment adversely affects the interaction between a functionalised primer and dentine collagen after acid-etching. Robust adhesion of marine mussels to their wet substrates instigates the quest for a strategy that improves the longevity of resin-dentine bonds. In the present study, an etching strategy based on the incorporation of biomimetic dopamine methacrylamide (DMA) as a functionalised primer into phosphoric acid etchant was developed. The mechanism and effect of this DMA-containing acid-etching strategy on bond durability were examined. Methods: Etchants with different concentrations of DMA (1, 3 or 5 mM) were formulated and tested for their demineralisation efficacy. The interaction between DMA and dentine collagen, the effect of DMA on collagen stability and the collagenase inhibition capacity of the DMA-containing etchants were evaluated. The effectiveness of this new etching strategy on resin-dentine bond durability was investigated. Results: All etchants were capable of demineralising dentine and exposing the collagen matrix. The latter strongly integrated with DMA via covalent bond, hydrogen bond and Van der Waals' forces. These interactions significantly improve collagen stability and inhibited collagenase activity. Application of the etchant containing 5 mM DMA achieved the most durable bonding interface. Conclusion: Dopamine methacrylamide interacts with dentine collagen in a humid environment and improves collagen stability. The monomer effectively inactivates collagenase activity. Acid-etching with 5 mM DMA-containing phosphoric acid has the potential to prolong the longevity of bonded dental restorations without compromising clinical operation time. Clinical Significance: The use of 5 mM dopamine methacrylamide-containing phosphoric acid for etching dentine does not require an additional clinical step and has potential to improve the adhesive performance of bonded dental restorations.